Subchronic toxicity and behavioural effects of Glycine max (L.) oil emulsion in male rats - M.A Akanmu; F.A. Orafidiya; S. A.Adekunle; E.M. Obuotor; S.A. Osasan (International Journal of Phytomedicine, 2011)
The oil of Glycine max commonly known as soybean oil has over the decades grown popularity for its low cholesterol hence its use within the household and commercially for food production has grossly increased. This study was aimed to determine the effects of long term consumption of soybean oil toxicologically and behaviourally. Male albino rats were administered with the vehicle, 5 and 10% oil emulsion for 30 days orally. The rats were subjected to behavioural tests such as novelty-induced behaviour (NIB), learning and memory tests and food intake measurement weekly. At the end of 30 days, rats were anesthetized and carefully dissected and blood sample was taken and analyzed haematogically and biochemically. The liver sample was also taken for biochemical analysis. Histopathological examinations were carried out on the brain, spleen, liver, kidney, lungs and testis samples. The results showed that oral administration of oil caused an increase in food intake, significant effect on NIB but had no effect on learning and memory. There was a significant (p<0.05) reduction in the level of both haemoglobin and PCV in the grouped administered with high dose. Biochemical analysis revealed a significant (p<0.05) increase in triglyceride, ALT, AST levels, with no effect on cholesterol. Histopathological analysis revealed no significant effects on the essential organs tested when compared with the vehicle treated rats. This study conclusively showed that soybean oil has central excitatory effects and there is need for caution when used for a long period since it has significant effects on biochemical parameters.